THE LIBERATION THEOLOGY OF ASGHAR ALI ENGINEER AND ITS RELEVANCE TO ISLAMIC EDUCATION OBJECTIVES - Misbachol Munir; Nida’ul Munafiah (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2018)
Abstract: Islamic education has a